Simulation and characterization of separate absorption and multiplication InGaAs/InP avalanche photodiode - Mahdi All Khamis (2023)
Avalanche photodiodes (APDs) are important components in the receiver module of the telecommunication system. Utilizing Indium Gallium Arsenide (InGaAs) as an absorption layer and Indium Phosphide (InP) as a multiplication layer makes the device suitable for optical fiber communication application especially in long haul communication system. The APD has gone through several evolutions in the last few decades. Each evolution has been with the purpose of increasing avalanche gain, frequency response and yield. This thesis reports a comprehensive work in designing the structure and evaluating the performance of the separate absorption, graded, charged and multiplication InGaAs/InP (SAGCM InGaAs/InP) through simulation of the APD device structure. The effect of multiplication layer width (MLW) and absorption layer width (ALW) on APD performance was studied and investigated. Silvaco TCAD software was used as simulation tools to simulate a precise model of InGaAs/InP APD and analyze its performance under illuminated conditions. As such, three different ALW with various MLW have been simulated while the structure of APD and material parameters were kept constant. It was found that in the APD with smaller MLW, the distance between the punch-through voltage and the breakdown voltage can be maximized. Therefore, the operation region of APD will be extended. In addition, the multiplication gain was calculated from the photocurrent and primary current by taking the APD collection efficiency effect under the consideration. One of the main challenges in this work was the precise physical parameters of the semiconductor materials for the simulation of dark current, photocurrent and impact ionization of the APD. Representing APD gain by considering the collection efficiency effect of APD was another major challenge. As such, extensive investigation has been performed and as a results a list of semiconductor material physical parameters which is suitable for (SAGCM) InGaAs/InP APD design using Silvaco ATLAS framework was fully established by correlating the simulation results to the experimental results. These physical parameters would be useful for future research work in optimizing the InGaAs/InP APD before going into actual semiconductor growth and APDs fabrication, which would significantly reduce the design cost of the APDs.